REDUCING THE BANDWIDTH OF SYMMETRICAL DISPERSED WOMBS WITH GENETIC ALGORITHMS - López Guevara, Ricardo (2011)
This work proposes the minimization of bandwidth in sparse symmetric Matrix, using genetic algorithms and an own software, developed in MS Visual Studio 6.0. There are very numerous applications both in Science and Engineering that requires the resolution of the minimization of bandwidth in symmetric sparse matrix. The solution of great systems of linear algebraic equations with dispersion, structured and symmetric coefficients, involves having great amounts of storage space and a large amount of computational time, The search space is N! in which N is the dimension of the matrix, which is usually quite large. This problem consists of finding a permutation of the rows and columns of a given sparse symmetric matrix, which keeps the nonzero elements in a band that is as close as possible to the main diagonal.